Utilizing a tectonic framework to constrain the mineral system and remobilization in the Kiruna mining district, Sweden - Logan, Leslie (Luleå tekniska universitet, Geovetenskap och miljöteknik, 2022)
The Kiruna mining district, located in the northern Norrbotten ore province, Sweden, is a geologically and economically important area, being the type-locality for Kiruna iron oxide-apatite (IOA) deposits and also host to a variety of other deposits including syngenetic stratiform exhalative Cu-(Fe-Zn) (Viscaria, Eastern Pahtohavare), epigenetic stratabound Cu ± Au (Pahtohavare), and iron oxide-copper-gold (IOCG, Rakkurijärvi) deposits. However, the timing of IOA versus IOCG within the tectonic evolution is in question based on structural investigations showing Cu- and Fe-sulfides occur in late-orogenic structures. Here we use an established tectonic framework to constrain mineral systems (tectonic/thermal drives, metal and ligand sources, fluid pathways, traps, remobilization mechanisms) related to the early and late phases of the Svecokarelian orogeny in the Kiruna mining district. U-Pb zircon geochronology of intrusions in the district indicates a thermal drive was present during the early phase of the Svecokarelian orogeny from ca. 1920-1865 Ma, however remains enigmatic for the late Svecokarelian orogeny. Zircon grains from a magnetite-ilmenite gabbro yielded an age of 1881 ± 8 Ma, coeval with the Kiirunavaara IOA deposit and suggested to represent an important generation of mafic magmatism related to the ore. Lithogeochemistry of early bimodal Svecokarelian intrusions in the district indicates a within-plate to active continental margin environment with a volcanic arc affinity, pointing to a back arc environment. Epsilon Ndi and 87Sr/86Sri values calculated from the U-Pb ages for the igneous intrusions were compared to samples of ore-related alteration from epigenetic Pahtohavare and Rakkurijärvi deposits, district greenstone, and Archean samples. Results show that each deposit sourced Sr and Nd from a variety of rocks suggesting broad fluid transport. Each deposit has a distinct Sr mixing trend suggesting they formed from different ore-forming fluids and pathways. This is supported by new structural data ...